Analisis Indeks Kepuasan Mahasiswa Pada Biro Administrasi, Keuangan, Perencanaan Dan Informasi (BAKPI) Universitas Kutai Kartanegara - Hartini, Maulina; Mawardi, Mawardi; Ningsih, Kartina Eka (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:The problem of that the researchers observed at BAKPI University of Kutai Kartanegara was still pretty much a look of discontent of students will be given during this service both in terms of the problem of the Ministry administration and procedures procedures service at BAKPI as a complaint against the procedure that is convoluted, the absence of a settlement period of certainty, the requirement that the lack of transparency, and the attitude of staff BAKPI less responsive.From the discussion at length on the subject of Community Satisfaction Index (IKM) of the Ministry's Bureau of Administration, finance, planning and information (BAKPI) University of Kutai Kartanegara requirements are in less good and less satisfying students. Visible results of IKM 60.71 value which means the quality of service the Bureau of Administration, finance, planning and information (BAKPI) University of Kutai Kartanegara overall less nice. Of the eight indicators that there are five indicators that still need to be improved terms of service, i.e. the time of service, managing information, managing behavior and the handling of the complaints advice to get good value for less, whereas the rest get aced i.e. procedure of service, type of product and service competence of implementors.So the hypothesis put forward in the previous chapters, namely